Flouting Relevance Maxim Benefits of Hillary Clinton's President Candidate Debate on 2016 - Agung Budi Kurniawan; Lilia Indriani (Journal of Pragmatics Research, 2023)
This research has an objective to analyze and reveal the benefits of flouting the relevance maxim of Hillary Clinton's speech in the 2016 USA candidate presidential debate. The data consist of the debate transcript which was taken from the Washington Post website, and a video that could be watched on YouTube. They are analyzed by confirming the relevance of semantic answers to every question within the context of speech. In the end, there are nine findings of the benefits of flouting the relevance maxim, which consists of increasing positive self-impression, avoiding giving direct agreement to a sensitive issue, closing potential negative attacks, decreasing the rival's credibility, guessing truthfulness, beating the rival's credibility, increasing effort to show positive personal credibility, telling the rival's past negative history, and proposing indirect conclusion. The findings are the implication of the complex use of verbal speech that is combined with action. The formal situation of the debate supports the maximum benefit of every flouting relevance maxim. The main conclusion of this research is that flouting the relevance maxim only sometimes negatively impacts both a speaker and an interlocutor. The impact is influenced by complex factors such as the background of the occasion, past conditions, and passion for an interaction.